A Model for Developing Curriculum Standards for Preschool Teacher Education - Pawilen, Greg Tabios (Philippine Journal of Education Studies (formerly the Education Quarterly); Vol 70 No 1 (2012): Education Quarterly)
This paper presents a model for developing curriculum standards for preschool teacher education especially for preschool teachers who will serve in different local communities in the Philippines. Different models of curriculum development were analyzed to come up with the proposed model for developing curriculum standards. The process of curriculum development in a teacher education institution for preschool education was also analyzed to understand how teacher education institutions develop curriculum and what curriculum sources and influences are considered when they develop curriculum. Curriculum experts in the Philippines and abroad were invited to give professional comments and to validate the model. The model for developing curriculum standards identified various curriculum sources and influences, and presents a logical, sequential, and dynamic procedure for developing curriculum. Keywords: curriculum development, standards, model, teacher education, preschool